The Able: A Campaign on Empowering Differently-Abled Individuals Towards Achieving Greater Sustainability in Malaysia - Jaya, Joana; Singh, Dihlvinder Kaur Mohkam; Vasudevan, Asokan; Mohamed, Saheera Sardar; Johan, Syahida; Rapiee, Mohamed Maliki Mohamed (Journal of Ecohumanism, 2024)
"The Able" campaign at INTI International University aimed to spotlight the challenges and experiences of individuals with disabilities, promoting an inclusive, empathetic, and accepting environment. Focusing on the individuality rather than the limitations of disabled persons, the initiative sought to educate, empower, and advocate for supportive legislation and awareness about equal opportunities. Utilizing plays, songs, PSAs, and panel debates, it addressed societal misconceptions and stigmas, pushing for a compassionate and inclusive approach in education and society. Panel discussions highlighted the barriers created by inaccessible infrastructure and societal prejudices, emphasizing the need for an inclusive culture. The campaign was grounded in compassion, knowledge, and empowerment, striving to debunk myths about disabilities through engaging activities and educational efforts, fostering community support, and advocating for equitable growth policies. Originating to increase awareness among university staff and students, the initiative emphasized the importance of integrating disabled individuals into all life aspects, supported by the Social Model of Disability. This model identifies societal, environmental, and attitudinal barriers as central to disability, advocating for supportive and diverse environments. Through qualitative methods and expert panel discussions, the campaign demonstrated a significant application of the social model in areas like lifestyle quality, education, inclusivity, and awareness. The positive reception of its media and the insightful panel debates highlighted the need for realistic representation and addressed the continuing challenges faced by students with disabilities, propelling the movement towards a more inclusive society.